THE RELATIONSHIP BETWEEN AGE, EDUCATION LEVEL, AND RESIDENTIAL AREA TOWARDS CONTRACEPTIVE USE IN MARRIED WOMEN IN INDONESIA - Nurussyifa Afiana Zaen (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2022)
Indonesia was the fourth most densely populated country in the world with more than 260 million people in 2017. One of the government's efforts to overcome the high rate of population growth is a family planning program by using contraception methods. However, the Contraceptive Prevalence Rate (CPR) for all contraception methods in Indonesia in 2017 was only 63.6%, lower than its target in 2017 which was 65.6%. Several previous studies have shown that there are factors that cause low contraceptive use, such as age, education, and residential area. This study aims to analyze the relationship between age, education level, and residential area with contraceptive use in married women in Indonesia. This study used secondary data from the 2017 IDHS with a cross-sectional design. The sample of this study was married women of 15-49 years old age group, with a total of 35,479 respondents. Data analysis used Chi-square statistical test. The results were the variables of age (p=0.000), education level (p=0.000), and residential area (p=0.008) showed statistically significant results. In conclusion, there are relations between age, education level, and residential area with contraceptive use in married women in Indonesia. Therefore, the coordination of cross-sectoral and cross-program needs to be carried out, such as intensifying the promotion and implementation of family planning programs in the community, socializing education about family planning, and equitable access to family planning services and information throughout Indonesia.